Pattern of Integrated System of Smallholder Beef Cattle Central in Tegal Regency - Aji Gunawan; Akhmad Sodiq; Krismiwati Muatip; Novie Andri Setianto (Buletin Peternakan, 2019)
Purpose of this research is to focus on importance of knowing the activities of smallholder enterprise systems, types and trends in the patterns of integrated systems adopted, the impact of implementing integrated systems and the implications for sustainability of livestock systems. This research also emphasize the importance of opportunities in enhancing and increasing livestock productivity and increasing production in smallholder farms and developing the easiest formulation of strategies for sustainable livestock systems. A qualitative method using Soft System Methodology (SSM) from System Thinking was chosen to visualize the activities of smallholder enterprise systems and the pattern of integrated systems are presented descriptively. The next study method of quantitative is used to determine the impact of livestock productivity on each applied integrated systems presented comparatively. Soft System Methodology succeed to visualize smallholder enterprise systems at the level of individual and community level of farmer. Farmer’s group activity  influence the pattern of integrated systems that impacted on beef cattle’s productivity. The ICLFS pattern promotes a way of optimally utilizing agroecosystems and it has potential and become candidate system that be able in enhancing and increasing productivity, increasing livestock production and farmer's income, and realize beef self-sufficiency.